AN OBESE PATIENT “PORTRAIT” BY THE RESULTS OF OUTPATIENT CARDIOVASCULAR REGISTRY “PROFILE” - A. V. Zakharova; Yu. V. Lukina; V. P. Voronina; S. N. Tolpygina; N. P. Kutishenko; N. V. Kiseleva; S. Yu. Martsevich (Кардиоваскулярная терапия и профилактика)
Aim. To assess the opportunities for registry methodology for comparative  evaluation of clinical and  anamnestic  characteristics of cardiological patients with and without obesity; to draw a “portrait” of the obese  patients, common for the cohort studied.Material and methods. The data  analyzed from outpatient  PROFILE registry during January  2011 to 31 august  2015: totally 1531 primary patient included, of those body mass index (BMI) collected in 1371. In 565 there was obesity of various grade, in 806 BMI was not higher than 30 kg/m2. The analysis done of retrospective data.Results. According to PROFILE results, obesity was found in 41,2% of patients, and those with obesity were younger (p=0,003). Among them men and women number was equa — 50,8% and 49,2%, resp. For the obese  there were characteristic  presence of dyspnea,  oedema  and low level of physical activity (p=0,0001). The obese  had 1,5-3 times more common  arterial hypertension,  2 type diabetes,  chronic heart  failure (p=0,0001),  glucose  tolerance  disordered  (p=0,001),  dyslipidemia (p=0,012). Regardless that the obese took medications more commonly (p=0,006), they more rarely reached  target level of blood pressure (BP), than those non obese (p<0,05). Almost nobody of those with obesity had prescribed  therapy against overweight, except 73 patients that participated in 2 clinical trials.Conclusion. The data from outpatient registry PROFILE has confirmed the main information on obesity in cardiological patients: a “portrait” is drawn of the obese, cardiovascular risk factors (CRF) formulated, and comorbidities. The data demonstrates more difficult achievement of target BP in the obese with regular medication treatment,  and highlights insufficient attention of physicians to diagnostics and especially treatment  of obesity, as underestimation of the overweight problem by patients themselves.